Interviews with elders of the Lutsel K'e Dene First Nation on Pikes Portage, the trail to the barren lands, 2010 - Dickson, Cindy; Parlee, Brenda; Catholique, Florence (Canadian Cryospheric Information Network, 2016)
Data consists of interviews carried out with elders in the community of Lutsel K'e and a field visit to Teho Æa Tué Xak'ethé took place in 2010 that included elders, adults and youth. : Purpose: The area has tremendous historic significance and continues to be an important cultural landscape. The work builds on research carried out under the West Kitikmeot Slave Study Society and the Ni Hat Ni program funded by the Cumulative Impact Monitoring Program (INAC). It provides a Denesoline perspective on the history of "Pikes Portage". : Summary: Not Applicable